Edukasi pembuatan kripik dari sukun dalam memanfaatkan potensi alam pada masyarakat kelurahan tanjung kasuari - Sonny Rumalutur; Stefany Martono; Luluk Suryani (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Tanjung Kasuari Village is one of the areas located in Southwest Papua. This sub-district is one of the places in Southwest Papua that has a lot of natural and tourist potential which can be utilized by the local community to meet their living needs. However, most people only take advantage of the tourism potential, namely the beauty of the beach as a tourist attraction. This can be seen from the large number of visitors to Tanjung Kasuari beach, especially on holidays. The community focuses more on serving tourists who visit the beach. For this reason, the PkM team conducted serveys and interviews regarding the obstacles faced related to the lack of utilization of natural potential. Based on the results of interviews with several sample residents, the community does not yet have ideas about utilizing natural potential. The team provided solution in the form of education, namely how to make and package chips from breadfruit which could become will be more creative and innovative in developing other natural potentials.